Geophonology of the Russian Language as a Part of Georusistic - Rudyakov А.Н.; Rudyakov Л.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The article is devoted to the analysis of the term «geophonology» from the standpoint of georusistics, which assumes the study of language units in the features of the modern global language space, within which the Russian language operates. The authors rely on the principles of linguistic functionalism, according to which language (including Russian) exists in several forms: «invariant» and «variants». The invariant is «language in general», a system of linguistic units and relations, which determine the opposition of one language to all other invariant languages; the variant is a form of invariant implementation under certain conditions. The article substantiates the necessity of taking into account the principal differences when considering the phonological system of the Russian language as a means of interactions within individual states, because it determines the variability in the realization of phonemes that are common for the Russian language in different positions, including the foreign language environment. It is the differences of this kind that determine the adaptation of the Russian language to the conditions that have developed on the territory of individual states and in which the social interaction of Russian-speaking population takes place today. In this regard, on the material of the Russian language, this article offers theoretical grounds for the establishment of the current and relevant model of geophonology, which reflects the features of interaction between Russian and other languages. Special attention is paid to the role of different manifestations of common phonemes, as they implement the language invariant in specific social, cultural, historical conditions, as well as within various states, which use the same language as a means of social interaction